A protocol for Italian validation of DEMQoL-Proxy Scale: assessing the Quality of Life of people with moderate or mild dementia. - Bonfigliuoli, Chiara; Miraglia Raineri, Alessandra; Foa’, Chiara; Guizzardi, Alessia; CATELLANI, ALICE; MANFREDINI , DEBORA; TRIPICCHIO , ILARI; DAVOLI , BARBARA; PITTI , GIOVANNI; TOJALLI , SHELSI; SALSI , MONICA; LO MASTRO , GIANLUCA; et al. (Acta Biomedica Atenei Parmensis, 2021)
In this paper, we propose an adaptation of a protocol for a tool’s validation. We have utilized this phases-theory to validate in Italian language an instrument to assess Quality of Life for people with moderate or mild dementia. We will explain the example of our Italian validation of DEMQoL-Proxy considering each De Vellis’s phase. We will explain our application of De Vellis’s model to Italian example described. For the first three phases, we reproduced the original validating study in which authors (Smith et al., 2005) defined what to measure, how generate a set of items and the structure of the scale. Indeed, for the last five phases we explained the adaptation of De Vellis’s model to Italian validation. We hope that this model could be effective to validating goals, for researchers and in particular for all professionals who deal with caregivers and patients with moderate and mild dementia. Furthermore, the measurement of the Quality of Life makes the scale widely useful within the various professional specialties and setting. Finally, thanks to the methodological assumptions adopted following the De Vellis’s eight-phase model, we can affirm that this first Italian pre-validation of the DEMQoL-Proxy seems to be an excellent forerunner for its effective validation in the Italian context.